Dead patents walking. - Heinze, W.F (IEEE spectrum)
With 562 US patents to his credit, Jerome Lemelson was the most prolific inventor since Thomas Edison (1093 patents). His inventions pop up in camcorders, VCRs, bar code readers, automated teller machines, machine vision systems, and more. But Lemelson, who died in 1997 at age 74, may have accomplished less than meets the eye. His detractors attribute much of his success to the use of Byzantine tactics for exploiting loopholes in the patent system. Even Arthur Lieberman, his former attorney, believes he simply had a knack for figuring out where an industry was headed, and then claiming that he had already been there. 'In many cases, Lemelson didn't patent inventions', Lieberman told Fortune magazine, 'he invented patents' . However, the loopholes in the patent process exploited by Lemelson, may be finally closing in on him. This paper briefly describes how Lemelson exploited the patent system and discusses a case in progress against the Lemelson Partnership regrading bar code patents